Educação humanizadora e desenvolvimento socioemocional: concepções agostinianas, docência e ações pedagógicas na Educação Básica - Bueno, Maciel Alves (2024)
The socio-emotional development of Basic Education students, recognized as mandatory since 2020, assumes great importance for education with a view to the development of citizens, aware of their role in society. In this sense, the work of Augustine of Hippo, about the relevance given to the meaning of interiority and the doctrine of the inner master, takes on special significance for students to understand the other and the world in interactive movement by involving the encounter with oneself and coexistence through an empathetic and altruistic attitude aiming at the good of all. This research aims to analyze the Augustinian conception of education in its conceptual dimensions and incorporation in the teaching-learning process, from the perspective of building a socio-educational culture that expands the process of development of the human being through emancipatory and liberating experiences aimed at social and personal transformation. The theoretical framework is based on works by Augustine that are located in the field of education, among other productions by authors who stand out in the educational area. The research is identified by the qualitative approach, having as methodological procedures the bibliographic investigation and document analysis. The document analysis will include legislation on public policies and documents that govern institutional actions in the field of school education. These procedures aim, in their specificities, to understand the possibility of socio-emotional development and its impacts on Basic Education. The methodological option also includes field research, carried out through semi-structured interviews, with a group of four teachers from the Colégio Agostiniano São José in the city of São José do Rio Preto – SP, intending to reflect on the understanding of Augustinian teaching practice and its articulation with the conception of education for interiority and otherness from the perspective of a critical and liberating consciousness